SWOT Analysis as a Strategy to Improve the Competitiveness of Ruby Corn Seeds PT. Advanta Seeds Indonesia - Deapati, Sabina Maipha; Zahro, Siti Fatimatus; Pratiwi, Vanessa Mutia; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to analyse the strategies employed by PT Advanta Seeds Indonesia for its Ruby seed products and develop new strategies by considering both internal and external factors, ultimately determining the most important alternative strategies. This research employs a descriptive qualitative approach, utilising IFE-EFE matrix analysis techniques, a SWOT matrix, and a QSPM matrix. The results of the SWOT analysis recommend that the company should implement a Strengths-Opportunities strategy, which includes two alternative strategies sorted by the QSPM matrix to determine the most important strategy. The results of the QSPM matrix rank three alternative strategies, namely Improving quality by developing new product innovations to overcome the threat of pests and diseases, as having the highest score of 6.945. The strategy of educating farmers on the importance of proper crop rotation to mitigate and break the chain of spreading pests and diseases has a score of 6.912. The strategy of improving product defect rates and offering more competitive prices to face competition and price fluctuations has a score of 6.826. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation and Infrastructure